Application of Combined Superficial Femoral Artery Stenting and Deep Femoral Artery Profundoplasty in Chinese Patients With Lower Extremity Artery Disease - Chi, Guoqing; Ding, Mingchao (Frontiers in Surgery, 2021)
Objective: Lower extremity artery disease (LEAD) increases sharply with age and results in severe burden of society and individuals. The current study aimed to compare the efficiency of simple superficial femoral artery stenting (SFAS) and hybrid operation, such as combined SFAS and deep femoral artery profundoplasty (DFAP), in the treatment of Chinese patients with LEAD classified as Rutherford grade 3-5. Methods: There were 200 patients with LEAD classified as Rutherford grade 3-5, including simple SFAS group (n=100) and combined SFAS and DFAP group (n=100). Results: All patients had median age of 71 years, and there were 143 males (71.5%). Not only increase rate of ankle brachial index (ABI), but also reduction rate of Rutherford grade were significantly higher after surgery in the combined SFAS and DFAP group than in the simple SFAS group (P<0.05 for all). Patency rate of patients in the combined SFAS and DFAP group was significantly higher than those in the simple SFAS group during the follow-up (P<0.05). Proportion of amputation and claudication distance＜200m had no significant difference between the two groups during the two-year follow-up (P>0.05 for all). Conclusion: The current study demonstrated that compared with SFAS, combined SFAS and DFAP improved not only ABI and Rutherford grade after surgery, but also patency rate during the follow-up, in Chinese patients with LEAD. Hybrid operation has significant value in alleviating clinical symptoms after surgery and improving vascular prognosis in Chinese patients.